“We missed the psychological support”: A case study about the preparation of the Brazilian bronze medal kata team for the 2019 Pan American Games - Paludo, Ana Carolina; Lassalvia, Cintia; Mazhak, Iryna; Cacek, Jan; da Silva, Danilo Fernandes (Frontiers in Psychology, 2023)
The main aim of the study was to describe the key factors involved in the preparation process of the Brazilian bronze medal kata team for the 2019 Pan American Games, focusing on the athletes’ perception. Three male athletes from the Brazilian team performed a semistructured interview to identify the following topics: specific time for preparation, training organization, supplementary support, and perception and suggestion about the efficiency of the preparation process. Data from interviews were gathered and coded, and the major themes were summarized as follows after performing content analysis of the data: a) technical and tactical training took the major part of the preparation; b) the high level of the coaches helped the team to reach the technical quality of the kata; c) better psychological support during the preparation could improve the athletes’ performance during the training and competition and d) the lack of financial support compromised the commitment of the athletes during the training routine. We concluded, based on the athletes’ perception, that the most positive factor during preparation for a major competition was the high amount of time focused on technical-tactical training. Even with limitations to performing the physical training, the athletes recognized the importance of the physical component, to increase performance. Financial and psychological support could have helped the team to reach a better result (gold medal) attenuating the training distress.